2017
DOI: 10.1093/bja/aex228
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopy versus direct laryngoscopy for adult patients requiring tracheal intubation: a Cochrane Systematic Review

Abstract: Difficulties with tracheal intubation commonly arise and impact patient safety. This systematic review evaluates whether videolaryngoscopes reduce intubation failure and complications compared with direct laryngoscopy in adults. We searched CENTRAL, MEDLINE, Embase and clinicaltrials.gov up to February 2015, and conducted forward and backward citation tracking. We included randomized controlled trials that compared adult patients undergoing laryngoscopy with videolaryngoscopy or Macintosh laryngoscopy. We did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
224
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(243 citation statements)
references
References 90 publications
8
224
0
11
Order By: Relevance
“…Thus, techniques that can reduce the number of attempts at endotracheal intubation and the duration of the procedure and minimize the proximity between the operator and the patient, should be prioritized, potentially reducing the risk of complications in hypoxic COVID-19 patients. In a systematic review including 64 studies and 7044 patients, video-laryngoscopy reduced the risk of failed intubation (OR 0.35, 95% CI 0.19-0.65), without a significant impact upon the proportion of successful first-pass attempts (OR 0.79, 95% CI 0.48-1.3), hypoxia (OR 0.39, 95% CI 0.1-1.44), or time for tracheal intubation [30,31]. In patients with difficult airways, the first-attempt success rate may be improved with video-laryngoscopy [32].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, techniques that can reduce the number of attempts at endotracheal intubation and the duration of the procedure and minimize the proximity between the operator and the patient, should be prioritized, potentially reducing the risk of complications in hypoxic COVID-19 patients. In a systematic review including 64 studies and 7044 patients, video-laryngoscopy reduced the risk of failed intubation (OR 0.35, 95% CI 0.19-0.65), without a significant impact upon the proportion of successful first-pass attempts (OR 0.79, 95% CI 0.48-1.3), hypoxia (OR 0.39, 95% CI 0.1-1.44), or time for tracheal intubation [30,31]. In patients with difficult airways, the first-attempt success rate may be improved with video-laryngoscopy [32].…”
Section: Rationalementioning
confidence: 99%
“…Summary of recommendations on the initial management of hypoxic COVID-19 patientsInvasive Mechanical VentilationRecommendation30. In mechanically ventilated adults with COVID-19 and ARDS, we recommend using low tidal volume (Vt) ventilation (Vt 4-8 mL/kg of predicted body weight), over higher tidal volumes (Vt > 8 mL/kg).…”
mentioning
confidence: 99%
“…A Cochrane database concluded that failed intubations were significantly fewer when videolaryngoscopy was used in patients with an anticipated difficult airway. 5 In our clinic, the need for fiberoptic intubation dramatically decreased after using the videolaryngoscopy in expected difficult airways.…”
Section: Discussionmentioning
confidence: 96%
“…Research into videolaryngoscope use has been complicated by the large number of different devices currently available, all classified as ‘videolaryngoscopes’, but with differing design, instructions for use and performance characteristics . In adults, different videolaryngoscopes have different performance profiles, with some outperforming others , and it is highly likely that the same is true in paediatrics and neonates. Although adult techniques cannot necessarily be transferred to paediatric practice, this is a fast‐moving field and it is likely that there will be an ongoing debate regarding videolaryngoscopy in paediatrics and neonatal practice in the next few years.…”
Section: Discussionmentioning
confidence: 99%